2014
DOI: 10.7326/m13-2844
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Aspirin for Prevention of Morbidity and Mortality From Preeclampsia: A Systematic Evidence Review for the U.S. Preventive Services Task Force

Abstract: Daily low-dose aspirin beginning as early as the second trimester prevented clinically important health outcomes. No harms were identified, but long-term evidence was limited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
360
0
29

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 428 publications
(396 citation statements)
references
References 72 publications
7
360
0
29
Order By: Relevance
“…W pierwszym i drugim trymestrze można rozważyć leczenie klasycznymi lekami z grupy NSAID (ibuprofen, indometacyna) [25][26][27]. Większość ekspertów preferuje duże dawki ASA, które stosuje się rutynowo w leczeniu zespołu antyfosfolipidowego u kobiet w ciąży i jest także umiarkowanie skuteczne w zapobieganiu rozwojowi stanu przedrzucawkowego u pacjentek obarczonych czynnikami ryzyka [224,225]. Po upływie 20. tygodnia ciąży podanie jakichkolwiek NSAID (z wyjątkiem ASA w dawce ≤ 100 mg/d.)…”
Section: Ciąża Okres Karmienia Piersiąunclassified
See 1 more Smart Citation
“…W pierwszym i drugim trymestrze można rozważyć leczenie klasycznymi lekami z grupy NSAID (ibuprofen, indometacyna) [25][26][27]. Większość ekspertów preferuje duże dawki ASA, które stosuje się rutynowo w leczeniu zespołu antyfosfolipidowego u kobiet w ciąży i jest także umiarkowanie skuteczne w zapobieganiu rozwojowi stanu przedrzucawkowego u pacjentek obarczonych czynnikami ryzyka [224,225]. Po upływie 20. tygodnia ciąży podanie jakichkolwiek NSAID (z wyjątkiem ASA w dawce ≤ 100 mg/d.)…”
Section: Ciąża Okres Karmienia Piersiąunclassified
“…może powodować zamknięcie przewodu tętniczego i wywołać upośledzenie czynności nerek płodu. Leki te powinno się bezwzględnie wycofać w 32. tygodniu ciąży [224,225]. Podczas całego okresu ciąży i karmienia piersią można podawać najmniejszą skuteczną dawkę prednizonu, stosując jednocześnie suplementację wapnia i witaminy D [25][26][27].…”
Section: Ciąża Okres Karmienia Piersiąunclassified
“…27 Full implementation of this intervention among all at-risk women could yield a 0.21-point reduction in the overall PTB rate (Fig 1). Other risk factors, specifically inadequate interpregnancy interval 28 and teen pregnancy, 29 have been shown to contribute to prematurity in the United States, although evidence-based interventions have not been proven and modeled for effect size.…”
Section: Reduction Of Early Elective Deliveries and Impact On Ptbmentioning
confidence: 99%
“…A very recent systemic review observed clinically important and statistically significant reductions in several important outcomes, but the investigators stated that their confidence was tempered by potential small-study effects and observed modest effects on outcomes in the 2 largest trials. 23 Depending on baseline risk, aspirin use was associated with absolute risk reductions of 2% to 5% for preeclampsia (RR ϭ 0.76; 95% CI ϭ 0.62-0.95), 1%-5% for intrauterine growth restriction (RR ϭ 0.80; 95% CI ϭ 0.65-0.99), and 2%-4% for preterm birth (RR ϭ 0.86; 95% CI ϭ 0.76 -0.98). The investigators did not observe different effects in trials in which aspirin was started before 16 weeks gestational age.…”
Section: Aspirin To Prevent Preeclampsiamentioning
confidence: 99%